IMPLEMENTATION OF INTEGRATED QUALITY MANAGEMENT STRENGTHENING CHARACTER EDUCATION IN REALIZING PANCASILA STUDENT PROFILES - Ade Dasmana; Iim Wasliman; ujang Cepi Barlian; Ricky Yoseptry (IJGIE (International Journal of Graduate of Islamic Education), 2022)
This research is motivated by the moral decadence of students related to various forms of juvenile delinquency such as fights between students, rampant cases of bullying, low levels of honesty, decreased ethics in attitudes and characteristics of identity to implement the norms and values ​​of Pancasila. This research approach is a qualitative research with case study method. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the planning of strengthening character education in realizing student profiles carried out by the school has shown quality because it has been stated in the RKS, Implementation of strengthening character education in realizing student profiles has not maximized work programs, Supervision of strengthening character education for Pancasila student profiles has shown quality to make activities Intra Curricular and extracurricular as a medium to build culture in all educational activities in schools, Evaluation has shown quality because it is carried out in two stages, namely short-term evaluation and long-term evaluation, Barriers to strengthening character education in realizing the profile of Pancasila students consist of internal and external obstacles, and The solutions that have been implemented have not shown quality because they have not been able to maximize the quality standards of improvement.